Grid resource data differentiation standard based on CIM model - Fupeng Li; Wenyuan Bai; Shaobo Liu; Yiming Zhang; Mingkang Guo (Scientific Reports)
Abstract Aiming at the problem of differential data processing of power grid resources, this paper puts forward a power grid data processing method based on Common Information Model (CIM) model. CIM integrates various departments of enterprises using modern computer technology, covering multiple links, and optimizes automation management in the manufacturing industry through the integration of software and hardware. By analyzing the characteristics and relations between single type and different types of power grid resource data, this paper stratifies and combines the power grid equipment and resources in CIM model, forming a brand-new data processing mode. This model can not only solve the problem of heterogeneity of power grid resource data, but also effectively integrate and process data from different sources and formats. In the process of data processing, regression analysis is used to adjust and optimize according to the actual data to ensure the accuracy and effectiveness of the data. The experimental results show that this method can significantly improve the efficiency and accuracy of data processing, and can better reflect the characteristics and status of power grid resources, which has high practical value.